(untitled) (Proceedings of International Educators Conference, 2024)
Uzbekistan, a country rich in history and culture, is also emerging as a promising destination for foreign investment. With a strategic location at the crossroads of Asia and Europe, Uzbekistan offers numerous tax incentives to attract international investors. This article explores the various tax incentives available to foreign investors in Uzbekistan, including exemptions, deductions, and reduced tax rates. By analyzing the tax landscape and investment climate, this article aims to provide a comprehensive overview of the opportunities and benefits for foreign businesses considering investment in Uzbekistan. Through case studies and practical examples, readers will gain insights into the tax incentives’ impact on investment decisions and learn how to navigate the Uzbek tax system effectively. Ultimately, this article serves as a valuable resource for investors, policymakers, and business professionals seeking to capitalize on Uzbekistan’s growing economy and favorable tax environment.